A tour of wood product manufacturing facilities in British Columbia as an example of experiential learning. Issue 1 (3rd December 2020) - Cool, Julie; Ellis, Simon; Jiang, Feng
Abstract: The provision of meaningful experiential learning opportunities for undergraduate students in natural resources‐based programs is particularly important. In 2017, the Department of Wood Science at the University of British Columbia reintroduced a dormant, 1‐week tour of manufacturing operations for students in the Wood Products Processing undergraduate program. This article describes the background to the reinstatement of the tour and some of the important logistical factors involved, including the timing of the tour in the academic calendar, the scheduling of manufacturing facilities visited, transport and accommodation considerations, and planning time at an outdoor education camp. The desired learning outcomes are discussed together with some of the challenges developing and enacting appropriate evaluations connected to them. An initial single, written technical report was later supplemented by evaluation components better connected to the desired experiential learning outcomes. Aspects of safety, participation, and punctuality were added, as were daily quizzes. The daily quizzes have evolved from paper‐based questions requiring statement responses to online, objective quizzes, which provided more timely feedback to students. The pros and cons of additional overview and/or summary sessions are discussed in relation to encouraging greater student engagement in achieving the desired learning outcomes.